2020
DOI: 10.1021/acscatal.9b03281
|View full text |Cite
|
Sign up to set email alerts
|

Observation of O–O Bond Forming Step of Molecular Co4O4 Cubane Catalyst for Water Oxidation by Rapid-Scan FT-IR Spectroscopy

Abstract: Monitoring of water oxidation by the established Co cubane catalyst Co4O4(OAc)4(py)4 (abbrev. Co4O4, OAc = acetate, py = pyridine) by time-resolved rapid-scan ATR FT-IR spectroscopy revealed the O-O bond forming intermediate by its O-O stretch mode at 833 cm-1. The catalysis was either driven in alkaline solution by a visible light sensitizer, or in hydroxide (OH-) containing acetonitrile solution using the one-electron oxidized cubane as the sole source of charge. The μ-peroxido structure of the intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
2
30
0
1
Order By: Relevance
“…Co III -OOH/Co III (CH 3 CO 2 H) mono ] 0 peroxide is ~762 cm -1 and is insensitive to O-OH to O-OD exchange(Table 2). Thus, this type of end-on peroxide also agrees with reported FT-IR29 . O-OH vibration (~807 cm -1 ) of the oxidized [Co III 2 O 4 Co IV -OOH/Co III (CH 3 CO 2 H) mono ] + form is highly plausible under applied potential and better agrees with the FT-IR experiment.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Co III -OOH/Co III (CH 3 CO 2 H) mono ] 0 peroxide is ~762 cm -1 and is insensitive to O-OH to O-OD exchange(Table 2). Thus, this type of end-on peroxide also agrees with reported FT-IR29 . O-OH vibration (~807 cm -1 ) of the oxidized [Co III 2 O 4 Co IV -OOH/Co III (CH 3 CO 2 H) mono ] + form is highly plausible under applied potential and better agrees with the FT-IR experiment.…”
supporting
confidence: 91%
“…Recent time-resolved rapid-scan IR observation of photo-oxidized cubane at pH=12.3 indicates no free acetate at reaction conditions, suggesting that all acetates remain at least as the terminal ligands to the cubane. 29 However, this observation contradicts the paper's following interpretations: assigning ~833 cm -1 band to Co-OO-Co peroxo species. Thus, we explored [Co III 2 O 4 Co IV =O/Co IV (CH 3 CO 2 ) mono ] 0 reaction with water via WNA mechanism which has negative (-0.27 eV) DG in the calculations done with 15% of Hartree Fock exchange (Table 1, Fig.…”
Section: The [Co IIImentioning
confidence: 72%
See 2 more Smart Citations
“…The in situ rapid-scan FT-IR spectroscopic investigations by Frei and co-workers indicated that the photo-driven water oxidation by Co 4 O 4 (Py) 4 (OAc) 4 cubane involves a Co III -(mperoxide)-Co III species at the O-O bond formation step, which is preceded by a Co III Co IV intermediate. 127 In 2017, our group reported a highly intact and stable Co-dpk (dpk: di(2-pyridyl)ketone) cubane WOC 45 ( Fig. 5), displaying the characteristic {H 2 O-Co 2 (OR) 2 -OH 2 } edge-site motif that catalyses photo-driven water oxidation.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%